Efectos de insecticidas usados en el maíz sobre los estados inmaduros de Trichogramma atopovirilia (Hymenoptera: Trichogrammatidae) - Braga Maia, Jader; Andrade Carvalho, Geraldo; Lopes de Oliveira, Rodrigo; Lasmar, Olinto [UNESP]; Santos Leite, Maria Isabella (My University, 2013)
The chemical control of Spodoptera frugiperda (Lepidoptera: Noctuidae) is difficult because caterpillars live inside the corn (Zea mays) cob and they do not come into contact with insecticides, Research on the use of parasitoids of the genus Trichogramma (Hymenoptera: Trichogrammatidae) has contributed to advances in alternatives for the control of this pest, However, there is little information on the effects of pesticides used in corn on these parasitoids, Therefore, the objective of this study was to evaluate the physiological selectivity of insecticides for Trichogramma atopovirilia in the egg-larval, pre-pupal and pupal phases, The bioassays were carried out under controlled conditions, exposing eggs of Anagasta (= Ephestia) kuehniella (Lepidoptera: Pyralidae) to parasitism for a 24-h period, The insecticides were sprayed using a Potter tower on host eggs containing the parasitoids in the egg-larval period, pre-pupal and pupal phases, The insecticides evaluated in g a, i, L-1 were: imidacloprid/ß-cyfluthrin (Connect 100™ SC - 0.033), chlorfenapyr (Pirate 240™ SC - 0.6), chlorpyriphos (Astro 450™ EW - 0.75), novaluron (Rimon 100™ CE - 0.05), spinosad (Tracer 480™ SC - 0.16) and triflumuron (Certero 480™ SC - 0.048), Water was used as a control, According to the results, the products were classified in the following toxicological classes for T, atopovirilia: imidacloprid/ßcyfluthrin, novaluron and triflumuron as harmless (class 1); spinosad and chlorfenapyr as slightly harmful (class 2); and Chlorpyrifos was harmful (class 4) to the parasitoid, Therefore, new studies under greenhouse and field conditions are necessary to confirm these toxicity results.
Effects of insecticides used in corn on immature stages of Trichogramma atopovirilia (Hymenoptera: Trichogrammatidae)
Keywords: Biological control; Parasitoids; Pesticides; Physiological selectivity; Zea mays